Artificial Intelligence Use Among Generation Z Students and Its Impact on Academic Performance and Learning Behavior - Alfi Rohmatul Hidayah; Farah Khoirunnisa; Kartika Nuswantara; Ratna Rintaningrum; Viona Fittria Sari; Aurelius Ratu (Jurnal Pendidikan dan Kebudayaan, 2026)
Artificial Intelligence (AI) has become a widely used tool among Generation Z students for completing academic tasks and exploring learning materials in the digital era. However, the responsible use of AI in producing academic work remains a subject of debate, particularly regarding its impact on students’ thinking processes and learning quality. This study aims to identify and classify patterns of AI use among Generation Z students and to examine the relationship between AI utilization and academic performance. The research employed a descriptive exploratory design using a mixed-methods approach. The participants were Generation Z students at Institut Teknologi Sepuluh Nopember (ITS), selected through stratified random sampling. The findings indicate that AI contributes significantly to improving assignment performance, academic productivity, and students’ confidence in participating in learning activities. Nevertheless, intensive AI use is also associated with shifts in learning behavior and motivation, from intrinsic curiosity toward performance-oriented and instrumental goals. These findings suggest that while AI enhances accessibility to information and learning efficiency, its use may reduce students’ engagement in reflective thinking, critical thinking, and collaborative learning processes. Therefore, ethical and pedagogical strategies for AI integration are needed to ensure that this technology supports academic competence development without diminishing the quality of student learning experiences.